Therapeutic efficacy of superficial vein-anastomosed spiral propeller flap in elderly patients with foot and ankle soft tissue defects - Chen, Guangmou; Liao, Zhidong; Ruan, Guoqiang; Chen, Huirun; Lv, Guihe; Cai, Jiashang; Chen, Jin; Liang, Bo (Frontiers in Surgery, 2025)
BackgroundThis study aimed to evaluate the efficacy of superficial vein anastomoses spiral propeller flaps in improving venous return and reducing postoperative complications for elderly patients with foot and ankle soft tissue defects.MethodsA prospective study involving 15 elderly patients (65–90 years) underwent spiral propeller flap repair between 2020 and 2021. Flap perfusion, swelling, venous patency (Doppler ultrasound), and ankle function (AOFAS score) were assessed.ResultsAll flaps survived, with 2 cases of distal superficial necrosis healing after dressing. Postoperative swelling improved from Grade II (n = 10) to Grade I (n = 13) at 6 months. AOFAS scores showed 86.7% excellent/good outcomes.ConclusionVenous anastomosis in spiral propeller flaps significantly enhances flap survival and functional recovery in elderly patients with comorbidities.